2022
DOI: 10.1155/2022/9094934
|View full text |Cite
|
Sign up to set email alerts
|

Application of Overlap Gastroduodenostomy in Billroth I Anastomosis after Totally Laparoscopic Distal Gastrectomy for Gastric Cancer

Abstract: Delta-shaped gastroduodenostomy (DSGD) and overlap gastroduodenostomy (OGD) are the two most widely used intracorporeal Billroth I anastomosis methods after distal gastrectomy. In this study, we compared the short-term outcomes of DSGD and OGD in total laparoscopic distal gastrectomy (TLDG). In a retrospective cohort study, we examined 92 gastric cancer patients who underwent TLDG performed by the same surgeon between January 2014 and June 2018. All patients underwent Billroth I reconstruction (OGD, n = 45; DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Some authors have expressed concern that an insufficient supply of blood to the duodenal wall between the transecting staple line and anastomotic staple line in DSG could be caused by unsuccessful transection of the duodenal bulb in a posteroanterior direction and the extensive dissection of supraduodenal vessels ( 11 , 17 , 21 25 ). Iwasaki et al ( 24 ) indicated that the twisting of the duodenal bulb at the posteroanterior transection is technically demanding.…”
Section: Intracorporeal Linear-stapled Gastroduodenostomy With Preser...mentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors have expressed concern that an insufficient supply of blood to the duodenal wall between the transecting staple line and anastomotic staple line in DSG could be caused by unsuccessful transection of the duodenal bulb in a posteroanterior direction and the extensive dissection of supraduodenal vessels ( 11 , 17 , 21 25 ). Iwasaki et al ( 24 ) indicated that the twisting of the duodenal bulb at the posteroanterior transection is technically demanding.…”
Section: Intracorporeal Linear-stapled Gastroduodenostomy With Preser...mentioning
confidence: 99%
“…We hypothesized that although the blood supply via the remnant cranial supraduodenal vessels is blocked by the anastomotic linear staple, the blood supply of this area in the DSG is assumed to be retained via the caudal supraduodenal vessels because the caudal and cranial supraduodenal vessels anastomosed at the anterior wall, that is, at the antimesenteric side (4,5). Some authors have expressed concern that an insufficient supply of blood to the duodenal wall between the transecting staple line and anastomotic staple line in DSG could be caused by unsuccessful transection of the duodenal bulb in a posteroanterior direction and the extensive dissection of supraduodenal vessels (11,17,(21)(22)(23)(24)(25). Iwasaki et al (24) indicated that the twisting of the duodenal bulb at the posteroanterior transection is technically demanding.…”
Section: Intracorporeal Linear-stapled Gastroduodenostomy With Preser...mentioning
confidence: 99%
See 3 more Smart Citations